Work-time control and exhaustion: internal work-to-home interference and internal home-to-work interference as mediators - Vieten, Laura; Wöhrmann, Anne Marit; Michel, Alexandra (International journal of environmental research and public health, 2022)
Strong work-time control (WTC) has been linked to reduced employee exhaustion, with work-to-home interference as an underlying mechanism. In this study, we aimed to investigate the mediation effect of both directions of internal work-home interference, namely internal work-to-home interference (IWHI) and internal home-to-work interference (IHWI). The analysis is based on data from the 2015, 2017, and 2019 BAuA-Working Time Survey, a representative German panel study. Cross-lagged panel models were estimated separately for IWHI and IHWI, based on the balanced panel (n = 3390). We investigated the hypothesized indirect as well as potential direct, reversed, and reciprocal effects of the constructs. WTC had a small but significant indirect effect on exhaustion via IWHI. Contrary to assumptions, WTC positively affected IHWI. Unexpectedly, there was no significant effect of IHWI on exhaustion. Hence, only IWHI was identified to mediate WTC’s effect on exhaustion. This implies that WTC helps employees avoid exhaustion from psychological preoccupation with work during free time. In addition, analyses suggested reversed and reciprocal relationships between the investigated constructs. Further investigation is needed to explore the role of psychological preoccupation with private matters during work time in the context of WTC and employee well-being.
Gesehen am 14.05.2022